Composición florística, estructura diamétrica y horizontal de un bosque de terraza baja, distrito de San Pablo, Loreto, Perú. 2024 - Mosquera Oversluijs, Luis Martin (2025)
A study was carried out on the floristic composition, as well as the diameter and horizontal structure of a low terrace forest, within the framework of the General Forest Management Plan (PGMF) No. 16-LOR-MAR/CON-MAD-2024-013, located in the district of San Pablo, Loreto. In total, 36 species distributed in 18 botanical families, 33 genera and 744 individuals were identified. The species Cedrelinga cateniformis and Calophyllum longifolium, which belong to the Fabaceae and Calophyllaceae families, were the most abundant, with 37 and 36 individuals recorded, respectively. The analysis of the diameter structure indicates that most of the trees have diameters ranging from 30 to 40 centimeters. This suggests a unimodal distribution, with a single maximum peak of 108 individuals, implying that the forest is predominantly composed of medium-sized trees. Furthermore, examination of the horizontal structure shows that the species Calophyllum longifolium and Cedrelinga cateniformis are the most ecologically relevant in this forest, with importance value indices of 13.94% and 13.86%, respectively. Statistical analysis reveals that the p-value (asymptotic significance) is 0,000, which is well below the usual significance threshold of 0,05. Therefore, the null hypothesis is rejected, allowing us to conclude that there is at least a significant difference in the average ranges of the horizontal structure variable among the different tree species present in the forest.